Self-Reported Health of Working-Age Refugees, Immigrants, and the Canadian-Born - McAlpine, Alyssa; Kobayashi, Karen; George, Usha; Fuller-Thomson, Esme (Advances in Public Health, 2022)
Canada has a rapidly growing refugee population, yet, there are limited research studies on the physical health of working-age refugees in comparison to the health of immigrants and Canadian-born individuals. Investigating social capital and acculturation measures may provide important insights into the factors associated with good self-reported health and this may help to inform health promotion strategies for refugees in Canada. A secondary analysis was conducted on data collected from the Canadian General Social Survey 27 (GSS-27) comparing a sample of refugees (n = 753), immigrants (n = 5,063), and Canadian-born (n = 11,266) respondents between the ages of 15 and 64. Both bivariate and logistic regression analyses were conducted. Self-reported physical health, dichotomized into poor versus good, was the outcome of interest. The self-reported physical health status of refugees, immigrants, and Canadian-born respondents was comparable. Visible minority status was not significantly associated with self-reported health status. Among refugees, the likelihood of reporting good health was associated with being a woman, being married/common-law, being involved in a social group/organization, and having more than half of one’s friends who spoke a different mother tongue than the respondent. Refugees, however, were less likely to have a confidant and be involved in social groups/organizations as compared to immigrants or those born in Canada. The odds of reporting good health were significantly lower among those who had experienced discrimination within the last five years. Social capital and acculturation may be protective of the self-reported health of refugees in Canada. Initiatives to support refugees’ social connections are therefore warranted.